suPAR to Risk-Stratify Patients With Malaria - Stefanova, Veselina; Crowley, Valerie M.; Weckman, Andrea M.; Kain, Kevin C. (Frontiers in Immunology, 2022)
Severe malaria (SM) is a leading cause of global morbidity and mortality, particularly in children in sub-Saharan Africa. However, existing malaria diagnostic tests do not reliably identify children at risk of severe and fatal outcomes. Dysregulated host immune and endothelial activation contribute to the pathogenesis of SM. Current research suggests that measuring markers of these pathways at presentation, may have clinical utility as prognostic indicators of disease progression and risk of death. In this review, we focus on the available evidence implicating soluble urokinase-type plasminogen activator receptor (suPAR) as a novel and early predictor of severe and fatal malaria and discuss its potential utility for malaria triage and management.